Child psychology in special children's development institution (LPKA): A legal perspective on hope and emotional balance - Ningsih, Dwi Wachidiyah (Journal of Law Science, 2025)
Children exercise of people's sovereignty in a direct democracy is realized through in the environment of coaching institutions are a vulnerable group that requires special attention. Limited access to education, psycho-social services, and an environment that is less supportive of children's growth and development can have a serious impact on long-term development. The objectives of this study are 1) to identify and analyze the psychological impact experienced by children behind the correctional institution, 2) to explore strategies in finding hope and efforts to maintain children's emotional balance in the situation at LPKA. 3) examine the role of law in providing protection and fulfillment of the rights of children in LPKA.  This study uses a qualitative legal research approach with a descriptive-analytical type, which is an approach that aims to deeply understand the subjective experience of legal actors in interpreting certain legal events or processes that focus on written legal norms (law in books), and law in practice (law in action). The results of this study are 1)  Children in LPKA show high potential for psychological resilience through counseling services, educational programs, religious activities, and communication with families, 2) Strategies in finding hope and maintaining children's emotional balance at LPKA can be done through counseling services, empowering education, religious and arts activities, and family support 3) National legal instruments have guaranteed the protection and fulfillment of children's rights at LPKA with policies that emphasize an educative and rehabilitative coaching approach.